Training course development of using English for classroom instruction of English teachers in primary school - WANNEE NIAMHOM (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The goals of this study were twofold: (1) to create and analyze a high-quality training course for English teachers in primary schools and (2) to test the efficacy of such a course in a real-world setting.Method: R&D used this research methodology in their efforts. The 28 primary school English teachers who participated in the training and analyzed the experiment’s results in using English in the classroom represented the research population. Frequencies, percentages, means, standard deviations, and the t-test were used to analyze the data.Findings: The findings of the research showed that: 1. the development and evaluation of the quality of the training course for using English to teach in a classroom was comprised of seven different components: 1) the curriculum’s theory and rationale, 2) the curriculum’s intended purpose, 3) the structure of the curriculum, 4) training units, 5) training approach, 6) training materials, and 7) assessment and assessment. While developing a leading training course for expert assessment, it was discovered that it was ideal and capable of leading for training purposes.Implications/Novel Contribution: The study’s goal is to create a curriculum for training English teachers in elementary schools to effectively use the language in the classroom, which will knock on students’ linguistic and cognitive development.